Corporate Social Strategy: Competing Views from Two Theories of the Firm - Bowen, Frances (Journal of business ethics, 2007)
This paper compares two theories of the firm used to interpret firms’ corporate social strategies in order to derive new insights and questions in this research area. Researchers from many branches of strategic management agree that firms can strategically allocate resources in order to achieve both long-term social objectives and competitive advantage. However, despite some progress in investigating corporate social strategy, studies rely on fundamentally diverging theoretical approaches. This paper will identify, compare and begin to integrate two competing theories of the firm implicit in corporate social strategy scholarship: the resource-based and behavioural theories of the firm. I discuss the implications of these two theories for both researchers and practitioners on key debates within corporate social strategy, and conclude by suggesting several fruitful avenues for future research based on the emerging integration of these two theories of the firm within the strategy literature.